Corporate Position in Election Crime: What is Corporate Criminal Liability According to Indonesian Positive Law? - Dewi, Lita Citra; Iryanto, Wisnu Pratama (Law Research Review Quarterly, 2018)
A corporation is a private legal entity that has its own entity and has the discretion in acting on behalf of the corporation. Included in the case of fraud opportunities that occur in elections. Corporations have a loophole to commit criminal acts in the upcoming 2019 elections. The form of corporate criminal liability is regulated by several laws that still apply in Indonesia. Penalties for business entities or corporations can be found in Article 83 paragraph (3) of Law 32/2004 concerning Regional Government, Article 116 paragraph (6) of Law 32/2004, Article 303 paragraph (1) of Law 8/2012 concerning Elections. In that article, it is explicitly stated that every person, group, company, and / or non-governmental business entity that provides election campaign funds exceeds the prescribed limits as referred to in Article 131 paragraph (1) and paragraph (2) shall be sentenced to a maximum imprisonment of 2 (two) years and a maximum fine of Rp. 5,000,000,000.00 (five billion rupiah). However, all of these rules must abide by the principle of Lex Posteriori derogate legi priori (the new rule removes the old rules) through Law number 7 of 2017 concerning Elections. This paper examines more deeply how an action can be categorized as an election criminal offense by a corporation and examines examples that have occurred in Indonesia.